2022
DOI: 10.3399/bjgp.2021.0715
|View full text |Cite
|
Sign up to set email alerts
|

Primary care contacts, continuity, identification of palliative care needs, and hospital use: a population-based cohort study in people dying with dementia

Abstract: Background: Reducing hospital admissions among people dying with dementia is a policy priority. Aim: To explore associations between primary care contacts, continuity of primary care and identification of palliative care needs with unplanned hospital admissions among people dying with dementia. Design & setting: Retrospective cohort study using the Clinical Practice Research Datalink linked with hospital records and Office for National Statistics data. Adults (>18 years) who died between 2009-2018 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Integrated models of care that help to ensure patients’ needs are met and care is delivered in the most appropriate setting 26 , may also reduce the need for emergency care. This is a particularly important consideration since Emergency Department visits for people approaching the end of life are increasing 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrated models of care that help to ensure patients’ needs are met and care is delivered in the most appropriate setting 26 , may also reduce the need for emergency care. This is a particularly important consideration since Emergency Department visits for people approaching the end of life are increasing 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrated models of care that help to ensure patients' needs are met and care is delivered in the most appropriate setting 24 , may also reduce the need for emergency care. This is a particularly important consideration since Emergency Department visits for people approaching the end of life are increasing 25 .…”
Section: Discussionmentioning
confidence: 99%
“…‘Dying well’ is also critical to ‘living well’. Many people with dementia become socially isolated, increasingly frail with repeated hospital admissions when they are dying from their dementia (Leniz et al., 2022). Good continuity of primary care has been shown to reduce these admissions towards the end of life (Leniz et al., 2022) and reduce recognised adverse health outcomes (Delgado et al., 2022).…”
Section: Definitionsmentioning
confidence: 99%
“…There is increasing evidence that continuity of care improves outcomes for PLWD. Studies have found that continuity of primary care results in lower rates of delirium and incontinence (Delgado et al., 2022) and better identification of palliative needs and fewer unscheduled hospital admissions (Leniz et al., 2022). Although recent primary care policy has perhaps prioritised access over continuity, for this vulnerable group with high healthcare need, consider promoting continuity of care and taking professional responsibility for these patients.…”
Section: Supporting People With Dementia To ‘Live Well’: Aa Suggested...mentioning
confidence: 99%